Reactions to Participation in Research on Violence Experiences and Minority Stress Among Sexual and Gender Minority Young Adults - Grocott, Lauren R. (Journal of interpersonal violence, 2023)
Given the growing body of research seeking to examine adverse childhood experiences (ACEs) and intimate partner violence (IPV) among sexual and gender minority (SGM) individuals, Institutional Review Boards must consider whether participating in violence research is emotionally distressing for SGM people. Yet, little research has studied SGM participants’ reactions to participating in research on ACEs, IPV, and minority stress. Thus, the current study examined reactions, including negative emotional reactions, to participating in violence research among SGM young adults. In total, 230 participants who self-identified as a sexual minority (30.1% also identified as a gender minority) in a dating relationship completed a cross-sectional assessment on ACEs, IPV (including identity abuse victimization and perpetration), minority stress (i.e., internalized homo/bi/transphobia), and reactions to research participation. Results indicated that participants identifying as a gender minority had significantly higher negative emotional reactions to study participation compared to cisgender participants, but this increase among gender minority individuals was small. In addition, gender minority participants and those with higher minority stress (i.e., internalized trans/bi/homo-negativity) and ACEs reported significantly higher negative emotional reactions to participation. Furthermore, gender minority participants scored worse on a scale indicating appreciation for contributing to research. Finally, reporting IPV victimization and perpetration was not associated with negative emotional reactions. Findings suggest that questions assessing minority stress and negative childhood experiences may be more emotionally salient or stressful for gender minority participants compared to questions measuring IPV.